Pengaruh Metode Chain Writing terhadap Keterampilan Menulis Siswa Kelas V Sekolah Dasar - Ai Parihah Ai; M. Fahmi Nugraha Fahmi; Anggia Suci Pratiwi Anggia (CENDEKIAWAN, 2020)
This study aimed to find out the effect of the implementation of the Chain Writing method on writing skills of grade V SDN Cisasah in learning to developing main ideas. This was a quantitative research with quasi experimental design. The basic consideration for using this design was that learning takes place naturally and the results obtained could be used to measure the effect of a treatment in the characteristics of the subject. The subject of this study were students grade V who came from two groups of students, namely the experimental group (implementing the Chain Writing method) and the control group. The data were collected through test technique divided two part, namely pretest and. The analysis technique this study was t-test. Based on this research showed that: (1) there are differences in the ability to writing skills to develop main ideas between students from experimental group with control group as evidence by the Sig. (2 tailed) is 0.00<0.05; and (2) there is an effect of implementing Chain Writing method for improving writing skills to developing the main ideas. Based on the mean value of the posttest results showed the experimental group is greater than the control group (83.70>57.90)